2013
DOI: 10.1111/nhs.12031
|View full text |Cite
|
Sign up to set email alerts
|

Multiple symptoms in patients with chronic obstructive pulmonary disease in Norway

Abstract: This paper examines the prevalence of multiple symptoms and the relationships between future expectations and multiple symptoms in a cross-sectional study of 100 patients with chronic obstructive pulmonary disease. A questionnaire was used to examine the patients' symptoms of breathlessness, anxiety, depression, sleeplessness, fatigue, and pain, and their outlook for the future. All patients reported breathlessness, 64% anxiety, 69% depression, 28% sleeplessness, 72% fatigue, and 45% pain. Those with anxiety r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 33 publications
1
35
1
Order By: Relevance
“…Pain was a common symptom in our study as in others 5,17,46 with no difference between those with moderate and severe airflow limitations. Close to one-fourth of the patients in each group reported that pain was quite a bit or very much distressing, but more patients with moderate airflow limitation used analgesics than those with severe.…”
Section: Msas Symptom Burden and Subscales Scoressupporting
confidence: 50%
See 1 more Smart Citation
“…Pain was a common symptom in our study as in others 5,17,46 with no difference between those with moderate and severe airflow limitations. Close to one-fourth of the patients in each group reported that pain was quite a bit or very much distressing, but more patients with moderate airflow limitation used analgesics than those with severe.…”
Section: Msas Symptom Burden and Subscales Scoressupporting
confidence: 50%
“…However, patients with COPD report that support from healthcare providers is rare concerning sleeping difficulties 45 . Multiple symptoms are known to catalyze and negatively affect each other 11 and thereby affect the quality of sleep 46,47 . Night-time symptoms and sleep disturbance are still "forgotten" dimensions in patients with COPD 48 that need more attention in care and research.…”
Section: Msas Symptom Burden and Subscales Scoresmentioning
confidence: 99%
“…Of the 14 articles on pain and symptom burden in COPD, three reports from Bentsen et al 9 21 22 and two reports from Borge et al 18 20 were based on the same original research study. Ten studies were conducted at the outpatient pulmonary department of a hospital (secondary and tertiary care), one in primary care and three were population-based studies.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of fatigue worsens as the disease progresses. [14,[17][18][19][20] Patients with COPD report worse psychological functioning and more psychiatric distress compared with patients with many other chronic diseases. [21,22] Prolonged illness such as COPD leads to changes in all aspects of a person's life.…”
Section: Introductionmentioning
confidence: 99%